Optimal charging coordination of plug-in electric vehicle incorporating capacitor and OLTC operation / Mir Toufikur Rahman - Mir Toufikur, Rahman (2018)
Electric utilities are concern with the impacts of new generations of smart appliances such as Plug-in Electric Vehicles (PEVs) on the performances, efficiency, stability and reliability of the distribution systems. It is well known that random PEVs charging activities in distribution system largely deteriorates the performance of the distribution system as it increases power loss, voltage deviation and transformer overload. As a result, the overall operational cost is increased significantly. These issues can be overcome by scheduling the PEV charging activities that decides which PEV will take charge in what time. Many researches have been carried out to mitigate the stated issues of distribution system by scheduling the PEV charging. This research proposes an optimal PEV charging coordination incorporating capacitor switching and on-load tap changer (OLTC) adjustment. The main consideration in this research is to minimize the daily power loss and voltage deviation. The capacitor and OLTC operation is utilized here in order to further improvement of voltage profile. It is found that, the proposed method gives minimum power loss and voltage deviation during the PEV charging activities. To implement the proposed method, two meta heuristic optimizations- binary particle swarm optimization (BPSO) and binary grey wolf optimization (BGWO) are employed. Apart from that, time of use electrical tariff is considered to minimize the charging cost when the PEV charging coordination is made. The proposed approach is coded in MATLAB and tested on modified 449 nodes residential distribution system. It consists of 22 low voltage feeders and each feeder has 19 nodes which represent each residential household. For the wide range of feasibility of the proposed method, different PEV penetration levels (16%, 32%, 47%, 63%) are studied. The simulation results for optimal PEV chargingcoordination incorporating capacitor switching and OLTC adjustment showed that proposed method reduced the system stresses and enhanced the performances of PEV charging coordination. Keywords: Plug-in Electric Vehicle, Coordination, Distribution system, Optimization, Charging cost.